Retrospective Analysis of Arthroscopic Superior Labrum Anterior to Posterior Repair: Prognostic Factors Associated with Failure - Rachel M. Frank; Shane J. Nho; Kevin C. McGill; Robert C. Grumet; Brian J. Cole; Nikhil N. Verma; Anthony A. Romeo (Advances in Orthopedics)
Background. The purpose of this study was to report on any prognostic factors that had a significant effect on clinical outcomes following arthroscopic Type II SLAP repairs. Methods. Consecutive patients who underwent arthroscopic Type II SLAP repair were retrospectively identified and invited to return for follow-up examination and questionnaire. Statistical analysis was performed to determine associations between potential prognostic factors and failure of SLAP repair as defined by ASES of less than 50 and/or revision surgery. Results. Sixty-two patients with an average age of years met the study criteria with a mean followup of 3.3 years. There were statistically significant improvements in mean ASES score, forward elevation, and external rotation among patients. Significant associations were identified between ASES score less than 50 and age greater than 40 years; alcohol/tobacco use; coexisting diabetes; pain in the bicipital groove on examination; positive O’Brien’s, Speed’s, and/or Yergason’s tests; and high levels of lifting required at work. There was a significant improvement in ASES at final followup. Conclusions. Patients younger than 20 and overhead throwers had significant associations with cases requiring revision surgery. The results from this study may be used to assist in patient selection for SLAP surgery.